Mergers in modern business - Stacey, Nicholas A. H. (London : Hutchinson, 1966)
This book focuses on mergers and acquisitions in Britain. Topics covered include why acquisitions arise, dilemma about redundancy, how to merge, reorganization by merger.
Includes bibliographical references and index
lje 25/04/17
Loans
Keywords: Consolidation and merger of corporations